Clinical effectiveness of decoction form of herbal medicine in primary care treatment of allergic rhinitis: A retrospective cohort study - Mi Ju Son; Sungha Kim; Young-Eun Kim; Bo-Young Kim; Chang-Sub Yeum; Jong Cheol Lee; Jae Hoon Cha; Soonsik Kang; Ching Hao Chang; Seokho Son (Integrative Medicine Research)
Background: The decoction form of herbal medicine (D-HM) is mainly prescribed to patients with allergic rhinitis (AR) in Korean Medicine (KM) clinics in the Republic of Korea; however, it is difficult to conduct clinical trials of D-HM due to regulatory issues. This study investigated the clinical safety and effectiveness of D-HM combination therapy for the treatment of AR by analyzing the AR outpatient data from 17 KM clinics. Methods: This retrospective cohort study included patients who visited KM clinics for AR treatment from January 1, 2021, to March 31, 2022. Cases were collated using structured case report forms and divided into the D-HM with KM usual care group (D-HM group) and the KM usual care group (UC group). Since D-HM therapy could not be randomly assigned to the study population, we used optimal propensity score (PS) matching to investigate the effectiveness and safety of D-HM combination therapy in the treatment of AR. Results: Data from 228 patients were collected. After PS matching, 144 patients were finally analyzed. The total nasal symptom score (TNSS) and mini-rhinoconjunctivitis quality of life questionnaire (mini-RQLQ) were significantly improved in the D-HM group compared with those in the UC group (TNSS: p=0.02; mini-RQLQ: p=0.04). Four patients in the D-HM group experienced minor adverse events that were mild and resolved within 15 days. Conclusions: D-HM combination therapy may be beneficial in the management of symptoms and rhinitis-associated quality of life and potentially useful in clinical practice. However, randomized placebo-controlled clinical trials are required to confirm their effectiveness. Study registration: This study has been registered at Clinical Research Information Service (KCT0007242).